OrpR is a σ54‐dependent activator using an iron‐sulfur cluster for redox sensing in Desulfovibrio vulgaris Hildenborough. Issue 1 (25th February 2021) - Fiévet, Anouchka; Merrouch, Meriem; Brasseur, Gaël; Eve, Danaé; Biondi, Emanuele G.; Valette, Odile; Pauleta, Sofia R.; Dolla, Alain; Dermoun, Zorah; Burlat, Bénédicte; Aubert, Corinne
Abstract: Enhancer binding proteins (EBPs) are key players of σ 54 ‐regulation that control transcription in response to environmental signals. In the anaerobic microorganism Desulfovibrio vulgaris Hildenborough ( Dv H), orp operons have been previously shown to be coregulated by σ 54 ‐RNA polymerase, the integration host factor IHF and a cognate EBP, OrpR. In this study, ChIP‐seq experiments indicated that the OrpR regulon consists of only the two divergent orp operons. In vivo data revealed that (i) OrpR is absolutely required for orp operons transcription, (ii) under anaerobic conditions, OrpR binds on the two dedicated DNA binding sites and leads to high expression levels of the orp operons, (iii) increasing the redox potential of the medium leads to a drastic down‐regulation of the orp operons expression. Moreover, combining functional and biophysical studies on the anaerobically purified OrpR leads us to propose that OrpR senses redox potential variations via a redox‐sensitive [4Fe–4S] 2+ cluster in the sensory PAS domain. Overall, the study herein presents the first characterization of a new Fe–S redox regulator belonging to the σ 54 ‐dependent transcriptional regulator family probably advantageously selected by cells adapted to the anaerobic lifestyle to monitor redox stress conditions. Abstract : Enhancer Binding Proteins (EBPs) are key players of σ 54 ‐regulation that control transcription of genes expression in response to environmental signals. OrpR is a novel type of EBP that presents an unprecedented Fe–S cluster in the PAS sensory domain and detects the redox potential, not O2 . In anaerobes, OrpR regulates the expression of genes crucial for growth in anaerobic conditions as a function of the redox potential of the environment.